Rekonstruksi Desain Kegiatan Laboratorium Indera Pengecap melalui Model ANCOR: (Reconstruction of Tastebuds Practical Laboratory Design through ANCOR Model) - Dewi Utami Tuzzahra; Sri Anggraeni; Bambang Supriatno (BIODIK, 2021)
Currently the world is entering the era of the 5.0 industrial revolution, people are required to have various 21st century skills in order to compete in this new era. This is a challenge for Indonesia to develop its education. Practicum is one of the solutions for develop 21st century skills. But turns out that it still has weakness caused by inappropriate practical laboratory worksheet. This study aims to analyze and to reconstruct the practical laboratory worksheet of the tastebuds. The research method used is descriptive qualitative research with the ANCOR model. The sampling technique used was purposive sampling, the sample consisted of 10 practical laboratory worksheet of taste buds from the 2006 KTSP curriculum to the 2013 revised curriculum. The instruments include conceptual, practical, and the construction of knowledge aspect adapted from the Vee diagram. The findings show that the practical laboratory worksheet of the taste buds still has problems from various aspects. Practical laboratory worksheet of tastebuds reconstruction is needed so that students are able to construct their knowledge properly through practicum activities carried out and develop 21st century skills. Abstrak. Saat ini dunia memasuki era revolusi industri 5.0 sehingga masyarakat dituntut untuk memiliki keterampilan abad 21 agar mampu bersaing di era baru ini. Hal ini menjadi tantangan tersendiri bagi indonesia dalam mengembangkan pendidikan. Praktikum merupakan salah satu solusi untuk membentuk keterampilan-keterampilan abad 21 ternyata masih memiliki kekurangan karena DKL yang tidak sesuai. Tujuan penelitian adalah menganalisis dan rekonstruksi DKL materi indera pengecap. Metode penelitian yang digunakan deskriptif kualitatif dengan model ANCOR (Analisis, Uji Coba dan Rekosntruksi). Teknik sampling yang digunakan yaitu purposive sampling, sampel terdiri dari 10 DKL indera pengecap dari kurikulum KTSP 2006 hingga kurikulum 2013 revisi. Instrumen yang digunakan meliputi instrumen aspek konseptual, praktikal, dan konstruksi pengetahuan yang diadaptasi dari Diagram Vee. Hasil temuan menunjukkan DKL indera pengecap masih memiliki masalah dari berbagai aspek sehingga diperlukan rekonstruksi DKL indera pengecap agar siswa mampu mengkonstruksi pengetahuannya dengan baik melalui kegatan praktikum yang dilakukan dan mengembangkan keterampilan abad 21.Â